Las autoridades utilizan programas espía y herramientas de extracción forense de Cellebrite para ‘hackear’ a periodistas y activistas - Amnesty International (Amnesty International, 2024)
La policía y las autoridades de los servicios de inteligencia de Serbia están utilizando programas avanzados de espionaje telefónico, junto con productos forenses para teléfonos móviles, para atacar ilegítimamente a periodistas, activistas ambientales y otras personas en una campaña de vigilancia encubierta, según ha revelado un nuevo informe de Amnistía Internacional.

Nigeria: Amnesty International petitions ICC judges to end Prosecutor’s delaying of justice for atrocity crimes - Amnesty International (Amnesty International, 2024)
Amnesty International today submitted a legal filing to the Pre-Trial Judges of the International Criminal Court (ICC) on behalf of several victims’ networks, to request an end to the ICC Prosecutor’s indefinite and unfathomable delay to the start of the court’s investigation into war crimes and crimes against humanity in Nigeria.

Authorities using spyware and Cellebrite forensic extraction tools to hack journalists and activists - Amnesty International (Amnesty International, 2024)
Serbian authorities are using spyware and Cellebrite forensic extraction tools to hack journalists and activists in a surveillance campaign.

Les autorités utilisent des logiciels espions et les outils criminalistiques d’extraction de données Cellebrite pour pirater des journalistes et des militantes - Amnesty International (Amnesty International, 2024)
Les services de police et du renseignement serbes utilisent un logiciel espion avancé, ainsi que des outils de criminalistique mobile pour cibler illégalement des journalistes, des militant·e·s écologistes et d’autres individus dans le cadre d’une campagne de surveillance secrète, révèle un nouveau rapport d’Amnesty International.